1993
DOI: 10.1002/ajhb.1310050412
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical growth and motor development in infancy and early childhood: Multivariate analysis

Abstract: This study was based on a sample of 651 singleton infants, from 325 unrelated families. Body weight (WT), length (LT) and head circumference (HC) of each child were measured at day of birth and thereafter every 3 months during the first 2 years. The achievement of five developmental milestones was surveyed, the ages at which the infant could turn him- or herself over (TURN), sit up (SAT), stand up (STOOD), walk without support (WALK), and cut the first tooth (TOOTH). Principal component analysis showed several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Livshits 12 also estimated associations between pairs of motor milestones. In that study phenotypic correlations were even lower than in Livshits et al 2 However, the common tendency of lowest correlation for TURN/WALK compared with the highest one for SIT/STAND has been replicated. Moreover, cross correlations obtained in the Livshits 12 study came out low and insignificant, in comparison with our findings that correlations ranged from 0.22 for TURN/WALK to 0.96 for SIT/STAND, with one exception (0.07 for TURN/WALK), all for MZ twins.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Livshits 12 also estimated associations between pairs of motor milestones. In that study phenotypic correlations were even lower than in Livshits et al 2 However, the common tendency of lowest correlation for TURN/WALK compared with the highest one for SIT/STAND has been replicated. Moreover, cross correlations obtained in the Livshits 12 study came out low and insignificant, in comparison with our findings that correlations ranged from 0.22 for TURN/WALK to 0.96 for SIT/STAND, with one exception (0.07 for TURN/WALK), all for MZ twins.…”
Section: Discussionmentioning
confidence: 46%
“…A direct relationship was found between sequential motor milestones (the most important predictor variable for each consequent milestone is the milestone already attained), and an indirect one with growth rate variables and birth measurements. 2 Social and demographic factors, in turn, did not indicate any significant relation to age of milestone achievement. 30,31 Anthropometric data did not influence the level of childhood motor development either.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Little is also known on measurement invariance; this indicates whether the scores of an assessment tool are equivalent across groups with different characteristics, which are known to have an influence on these milestones ( Tenovuo et al, 1988 ; Livshits et al, 1993 ; Flensborg-Madsen and Mortensen, 2017 ). For instance, previous literature has shown that gestational age and birth weight are related to motor milestones ( Pin et al, 2010 ; da Costa Ribeiro et al, 2017 ; Flensborg-Madsen and Mortensen, 2017 ; van Dokkum et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%